Efisiensi Produksi Dan Income Over Feed Cost Usaha Ternak Sapi Po Melalui Pemanfaatan Pakan Murbei - Duta Setiawan (Jurnal Riset Agribisnis dan Peternakan, 2016)
Based on agricultural production, Indonesia has very high potential to increase mulberry production through the implementation of adapted and liable technology. The research was conducted to study the ability of mulberry leave meal addition concentrates on the performance of Ongole Grade. This experiment used a randomized block design, with 4 treatments and 4 blocks. Treatments consisted of P1 (native grass and concentrate feed in the form of mulberry leaves meal and concentrate completely), P2 (native grass and concentrate feed in the form of mulberry leaves meal and corn concentrate), P3 (native grass and concentrate feed in the form of mulberry leaves meal and rice bran concentrate), P4 (native grass and concentrate feed in the form of mulberry leaves meal and concentrate tapioca waste). The experiment was conducted for 4 months with the adaptation periods for 2 weeks. Parameters measured were feed consumption, daily body weight gain, feed efficiency, Income Over Feed Cost (IOFC), revenue cost ratio. The results showed that the mulberry leave meal addition on different concentrate did not significantly (P>0,05) affect daily body weight gain, feed consumption, feed efficiency and Income Over Feed Cost (IOFC), and revenue cost Ratio. It is concluded that based on the nutrient digestibility, mulberry leaf meal concentrate can be combined with a single concentrate such as corn, cassava waste meal, or complete concentrate.